STOMACH CONTENTS AND INDEX OF FOOD SIGNIFICANCE OF PARACHANNA OBSCURA (GÜNTHER) IN KIRI RESERVOIR, SHELLENG, ADAMAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The study was conducted to investigate the stomach content and index of food significance of Parachanna obscura, in Kiri reservoir, Shelleng, Adamawa state, Nigeria for a period of six months from May to October, 2015. A total 62 fish were collected on the landing site, caught by gill nets of various stretched mesh sizes. In which 46 (74.19 %) had contents with various degree of fullness, while 16 (25.81 %) specimens had empty stomachs. The stomach contents were analyzed using frequency of occurrence, Relative Frequency and the Point’s method. The food items in the stomach covered a wide variety, ranging from various types of Algae to insect parts. The major food items in terms of frequency of occurrence were pithopora and spirogyra had 60.87 % and 55.52 % respectively, which made them the most frequent in occurrence, insect parts appeared the least, with a 10.87 % frequency of occurrence. The Relative Frequency showed that volvox had the highest with 13.07 % while insect parts had the lowest with 0.82 %. The Index Food Significance (IFS) of P. obscura shows that Filamentous Algae and Colonial Algae are the secondary diet of the species, spirogyra (IFS=1.42 %), Pithopora (IFS=1.51 %), Ulothrix (IFS=1.10 %), Volvox (IFS=1.56 %), while its incidental diet include Green Algae, Cyanobacteria and Diatom, with IFS of
Keywords: stomach content, index of food significance, Parachanna obscura, Kiri Reservoir